Pre-Service Teachers' Knowledge of Pedagogy in Mathematics Learning on The Topic of Special Angles in High School - M. Ma'rufi; Fahrul Basir; Rio Fabrika (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2021)
This research is a case study that adopted a qualitative approach. It took place in the tenth-grade classes of MAN Palopo. The study's objective was to investigate pre-service teachers' knowledge of pedagogy during mathematics teaching and learning on the topic of unique angles in Trigonometry. The participants recruited showed distinct tendencies in every aspect observed. Participants had the skill in representing the problems through visual and verbal representation. Besides, they also tackle the problem of students' misconceptions by explaining the procedures. The participants used to encourage students to express the reasons for the use of methods. Lastly, knowledge of how to teach a concept facilitated by good class management could minimize misconceptions and enable meaningful learning for students.